Ultrastructural and Immunohistochemical Studies of Transplanted Canine Lung Carcinoma Cell to Severe Combined Immunodeficiency Mice (STUDI ULTRASTRUKTUR DAN IMUNOHISTOKIMIA TRANSPLANTASI SEL KANKER PARU-PARU ANJING PADA MENCIT SEVERE COMBINED IMMUNODEFF - Sari, Dwi Kesuma; Priosoeryanto, Bambang Pontjo; Agungpriyono, Dewi Ratih; Yamaguchi, Ryoji; Uchida, Kazuyuki; Tateyama, Susumu (Jurnal Veteriner; Vol 14 No 4 (2013), 2013)
Primary lung cancers, or tumors originating in the lung, are relatively uncommon in dogs. The objectiveof this study was to describe the canine lung carcinoma that serially transplanted into severe combinedimmunodeficiency (SCID) mice, in order to established cell line from this tumor cell.  Morphology andcharacteristic of this canine lung carcinoma in SCID mice by histopathological and ultrastructuralexaminations with metastatic lesion in lung were also examined.  Histopathologically, the tumor masswere consisted of cuboidal to columnar cells with papillary pattern, uniform in size, the nuclei were oftenvariable in size, and some cells have vacuole on their cytoplasms.  Glandular forms were predominant withlobulated pattern, ductal pattern with papillary injected into tube-like structure were also encountered.Mitotic figures commonly found with inflammatory reaction were sometimes present in the interstitiumand lumen gland.  Ultrastructural analysis of the tumor cells showed round to oval cells with one or moreprominent nucleoli.  The cells possessed numerous mitochondria, smooth endoplasmic reticulum, andindividual cells which were interconnected via desmosomes.  Tonofilament characterize by long cytoplasmicmaterial was encountered.  Positive reaction of the round to oval tumor cells to anti keratin antibodyconfirmed that their epithelial cell nature.  Lung metastatic lesions were found in SCID mice aftertransplantation and this phenomenon indicated that canine lung carcinoma is tumorigenic to SCID mice.
Keywords: canine lung carcinoma, cell culture, SCID mice, metastasis, immunohistochemistry